From wastewater to resistance: characterization of multidrug-resistant bacteria and assessment of natural antimicrobial compounds - Li, Mingyue; Zhan, Angela; Rahman, Tahira Tasneem; Jiang, Tao; Hou, Liyuan (Frontiers in Microbiology, 2025)
The development and spread of antibiotic resistance in wastewater pose significant threats to both the environment and public health. Bacteria harboring multiple antibiotic resistance genes (ARGs), including those associated with horizontal gene transfer (HGT), can serve as persistent reservoirs and vectors for antimicrobial resistance in natural ecosystems. In this study, nine antibiotic-resistant bacterial strains (U1–U9) were isolated from a wastewater treatment plant (WWTP) effluent. The isolates were identified using 16S rRNA gene sequencing and whole-genome sequencing (WGS), and their antibiotic susceptibility profiles were evaluated. All isolates exhibited resistance to multiple antibiotics, and WGS revealed that U1, U2, U4, and U7 harbored diverse ARGs, including β-lactamase genes, efflux pumps, and resistance determinants for sulfonamides, tetracyclines, and, quinolones, confirming the presence of multidrug-resistant bacteria in WWTP effluent. Phylogenetic analysis classified them into Microbacterium spp. (Actinobacteria), Chryseobacterium spp. (Bacteroidetes), Lactococcus lactis spp. (Firmicutes), and Psychrobacter spp. (Proteobacteria). To explore mitigation strategies, eleven natural compounds were screened for their effects on cell growth, biofilm formation, and motility in selected multi-drug-resistant bacteria. Among the tested compounds, curcumin and emodin showed the most consistent inhibitory activity, particularly against Microbacterium spp. strains U1 and U2, and Lactococcus lactis sp. U4. In contrast, Chryseobacterium sp. U7, a Gram-negative strain, exhibited strong resistance to all tested natural compounds, highlighting the challenge of controlling Gram-negative ARBs in wastewater settings. These findings underscore the environmental risks posed by multidrug-resistant and HGT-associated ARG-harboring bacteria in WWTP effluent. They also demonstrate the potential of natural products, such as curcumin and emodin, as alternative or complementary agents for mitigating antibiotic resistance in water systems.